Digitalizacja filozofii formalnej - Garbacz, Paweł (Filozofia Nauki, 2016)
The paper presents a case study of digitalisation of formal philosophy. Using the theorem provers available at www.cs.miami.edu/ tptp/cgi-bin/SystemOnTPTP, I show that the formal ontology presented in (Nieznański 2007) is inconsistent. I also discuss some ways to avoid this inconsistency.